A Black Swan in the district? An IMP perspective on immigrant entrepreneurship and changes in industrial districts. Issue 2 (13th June 2016) - Milanesi, Matilde; Guercini, Simone; Waluszewski, Alexandra
Abstract : Purpose: – The purpose of this paper is to discuss the changes of the Italian textile district of Prato, considered an exemplary case of the industrial district (ID) model, using a business network perspective. The "Black Swan" metaphor is used to address the changes in the Prato textile district in order to understand whether such changes have been an unexpected and unpredictable phenomenon, or they can be explain with a different theoretical tool-box, namely, that developed by the industrial network approach. Design/methodology/approach: – The paper utilizes already published studies on the changes of the textile/fashion companies located to the Prato area. Both studies that have been carried out within an ID approach and those carried out with an Industrial Marketing and Purchasing (IMP) point of departure are considered in the research. Both types of studies were utilized to identify empirical observed changes of the producer, respectively user setting that the Prato located companies was related to, including identification of changes affecting both the local setting and the larger network it was related to. Findings: – The utilization of the IMP model proposes a learning ground that exceed the local context and open ups of investigations of opportunities and threats stemming from interactions across spatial borders. Analysed from an interactive point of view, in the specific context of Prato, the exploitation of the opportunities given by establishing relationship between natives and migrants actors goes through the creation of interactions among actors representing specific resource combinations and activity structures – within and outside the local community. Originality/value: – The paper concerns how the same research object – the changes of the Prato district – appears from another perspective different from the ID theory, namely, the industrial network approach developed by scholars of the IMP Group.